ENHANCING THE QUALITY OF EDUCATION THROUGH THE RESPONSIBILITY AND INNOVATIVE APPROACHES OF LITERATURE TEACHERS - Andaqulova Gulnora Mirzaanvarovna (Modern American Journals, 2025)
The stability and progress of society largely depend on the quality of education. In particular, the subject of literature plays a crucial role not only in imparting knowledge but also in shaping students’ thinking, aesthetic taste, spirituality, and national pride. A literature teacher with modern pedagogical approaches, broad literary insight, and the ability to inspire independent thinking among students is considered the cornerstone of quality education. This article discusses the role, responsibility, and methodological mastery of literature teachers in the educational process, as well as their contribution to improving the quality of education.
Keywords: Literature, spirituality, quality of education, teacher’s mastery, independent thinking, innovative method, creativity.